HYSTERIC outline of a figure. - Bowen, Eleanor; González, Laura (Artist) ([S.l.] : ROUTLEDGE, 2023)
Examining historical, clinical, and artistic material, in both written and visual form, this book traces the figure of the contemporary hysteric as she rebels against the impossible demands made upon her. Exploring five traits that commonly characterise the hysteric as an archetype - a specific body, mimetic abilities, a shroud of mystery, a propensity to disappear, and a particular relationship to voice - the authors shed light on what it means to be hysterical, as a form of rebellion and resistance. This is important reading for scholars of sociology, gender studies, cultural studies, and visual studies with interests in psychoanalysis, art, and the characterisation of mental illness.
Keywords: Hysteria in literature; Hysteria in art; Hysteria -- Social aspects; Women and psychoanalysis; Women -- Social conditions; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General